Innate immunity in peripheral tissues is differentially impaired under normal and endotoxic conditions in aging - Noh, Ji Yeon; Han, Hye Won; Kim, Da Mi; Giles, Erin D.; Farnell, Yuhua Z.; Wright, Gus A.; Sun, Yuxiang (Frontiers in Immunology, 2024)
Chronic low-grade inflammation is a hallmark of aging, aka "inflammaging", which is linked to a wide range of age-associated diseases. Immune dysfunction increases disease susceptibility and increases morbidity and mortality in aging. Innate immune cells, including monocytes, macrophages and neutrophils, are the first responders of host defense and the key mediators of various metabolic and inflammatory insults. Currently, the understanding of innate immune programming in aging is largely fragmented. Here we investigated the phenotypic and functional properties of innate immune cells in various peripheral tissues of young and aged mice under normal and endotoxic conditions. Under the steady state, aged mice showed elevated pro-inflammatory monocytes/macrophages in peripheral blood, adipose tissue, liver, and colon. Under lipopolysaccharide (LPS)-induced inflammatory state, the innate immune cells of aged mice showed a different response to LPS stimulus than that of young mice. Moreover, LPS-induced immune responses displayed differential profiles in different tissues and cell types. In the peripheral blood, when responding to LPS, the aged mice showed higher neutrophils, but lower pro-inflammatory monocytes than that in young mice. In the peritoneal fluid, while young mice exhibited significantly elevated pro-inflammatory neutrophils and macrophages in response to LPS, aged mice exhibited decreased pro-inflammatory neutrophils and variable cytokine responses in macrophages. In the adipose tissue, LPS induced less infiltrated neutrophils but more infiltrated macrophages in old mice than young mice. In the liver, aged mice showed a more robust increase of pro-inflammatory macrophages compared to that in young mice under LPS stimulation. In colon, macrophages showed relatively mild response to LPS in both young and old mice. We have further tested bone marrow derived macrophages (BMDM) from young and aged mice, we found that BMDM from aged mice have impaired polarization, displaying higher expression of pro-inflammatory markers than that from young mice. These data collectively suggest that innate immunity in peripheral tissues is impaired in aging, and the dysregulation of immunity is tissue-and cell-dependent. Our findings in the rodent model underscore the complexity of aging immunity. Further investigation is needed to determine whether the immune profile observed in aged mice is applicable in age-associated diseases in humans.